FEATURES OF HLA-DRB1 AND DQB1 ALLELES DISTRIBUTION IN CHILDREN WITH GENERALIZED TUBERCULOSIS - A. A. Starshinova (SPb RAACI, 2017)
So far, there is no clear understanding for the reasons causing tuberculosis generalization in children. Development of generalized infection could be also determined by some features of immune response which may depend on genetic markers. The aim of our work was to study the features of HLA-DRB1 and HLADQB1 allele distribution in children with generalized tuberculosis (gTBC). Materials and methods: we have observed 40 children at the age of 1 to 15 years suffering from gTBC. After performing a standard phthysiatric examination, including molecular-genetic diagnostics of surgical material, multispiral CT, immunological testing, as well as HLA-DRB1 and DQB1 alleles. We have studied distribution of the HLA-DRB1 and DQB1 alleles comparing it with a group of healthy donors (n = 100).The results did not show significant differences in HLA-DQB1 allele distribution between the gTBC patients and comparison group. Meanwhile, when comparing genotypes for HLA-DRB1 loci, we have revealed a significantly lower prevalence of the *01 allele of HLA-DRB1 (12.5% versus 31.0%; χ2 = 4.08; р < 0.05), which could be considered a predisposing factor, as well as a higher incidence of *14 allele (7.5% against 1.0%; χ2 = 3.67, р < 0.05) of HLA-DRB1 gene, thus suggesting its protective role.Conclusions: we did not find any significant differences for HLA-DQB1 distribution between pediatric patients with generalized tuberculosis and healthy donors, whereas * 01 allele of HLA-DRB1 may predispose for gTBC, and the *14 allele could be protective in evolving generalized tuberculosis in children.